PENGARUH DEBT TO EQUITY RATIO TERHADAP DIVIDEND PAYOUT RATIO MELALUI RETURN ON ASSET - Rahmat Agus Santoso; Anita Handayani (Jurnal Manajerial, 2019)
Dividend distribution becomes a complicated problem due to differences in interests between management and shareholders. Dividends are part of the profits obtained by the company during its business which are distributed to shareholders. The dividend payout ratio determines the amount of profit divided into cash dividends and retained earnings. If the retained earnings of the company are large, the profit to be paid as a dividend will be smaller. Important aspect of dividend policy is determining the appropriate profit allocation between payment of earnings as retained earnings and earnings as dividends. Analysis of the data used in this study uses Partial Least Square (PLS). Debt to Equity Ratio (DER) has a significant negative effect on Return on Assets (ROA). Debt to Equity Ratio (DER) does not directly influence Dividend Payout Ratio (DPR). Return on Assets (ROA) has a significant positive effect on Dividend Payout Ratio (DPR). Return on Assets (ROA) is not able to mediate between Debt to Equity (DER) with Dividend Payout Ratio (DPR).